P‐6.6: Effect of SiO2/SiNx/Resin Multi‐layer on the TFT Characteristics of BCE‐Type IGZO‐TFT. (26th August 2021) - Xu, Dezhi; Duan, Xianxue; Liu, Tianzhen; Gong, Kui; Zhang, Zhihai; Shi, Yue; Hu, Jing; Wang, Sheng; Lee, SeungKyu; Wang, Zhangtao
Abstract : In this paper, the influence of organic resin design on TFT characteristics is discussed. From the comparison of TFT characteristics, it can be concluded that the coverage of resin (full and partial) can solve the conductive trend of BCE a‐IGZO TFT. Combined with SiNx and SiO2 in organic resin buffer layer process adjustment, Vth can be controlled at about 1.5V.